2022
DOI: 10.1007/s00381-022-05571-y
|View full text |Cite
|
Sign up to set email alerts
|

Dose-dependent seizure control with MEK inhibitor therapy for progressive glioma in a child with neurofibromatosis type 1

Abstract: Background Low-grade gliomas (LGGs) occurring in children can result in many different neurologic complications, including seizures. MEK inhibitors are increasingly being used to treat LGG, but their effect on associated neurologic symptoms has not been established. Results Here, we report a patient with neurofibromatosis type 1 (NF1), medically refractory epilepsy (MRE), and an extensive optic pathway glioma (OPG) who developed dose-dependent seizure cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
0
5
1
Order By: Relevance
“…In terms of clinical findings, a recent case report described use of a MEK inhibitor (i.e., selumetinib) to treat a progressive optic pathway glioma in child with neurofibromatosis type 1 who also had medically refractory epilepsy. This patient showed resolution of seizures upon initiation of therapy with reemergence of seizures after dose reduction and subsequent cessation of seizures upon return to full dose (Cantor et al, 2022)…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In terms of clinical findings, a recent case report described use of a MEK inhibitor (i.e., selumetinib) to treat a progressive optic pathway glioma in child with neurofibromatosis type 1 who also had medically refractory epilepsy. This patient showed resolution of seizures upon initiation of therapy with reemergence of seizures after dose reduction and subsequent cessation of seizures upon return to full dose (Cantor et al, 2022)…”
Section: Discussionmentioning
confidence: 89%
“…In terms of clinical findings, a recent case report described use of a MEK inhibitor (i.e., selumetinib) to treat a progressive optic pathway glioma in child with neurofibromatosis type 1 who also had medically refractory epilepsy. This patient showed resolution of seizures upon initiation of therapy with re‐emergence of seizures after dose reduction and subsequent cessation of seizures upon return to full dose (Cantor et al, 2022). Similarly, another study reported reductions in seizures in response to the MEK inhibitor trametinib in two RASopathy patients with treatment‐resistant epilepsy, including one patient carrying a p.F595L germline variant in BRAF (D'Onofrio et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…This patient had a bilateral OPG with extension into the hypothalamus, basal ganglia, and subcortical white matter, as well as a mass effect on the right insular cortex and focal symptomatic epilepsy lateralized to the right hemisphere. Repeat brain MRIs after treatment by MEKi revealed a stable mass size but interval reduction in enhancement of the right frontal lesion suggestive of a treatment response 30 …”
Section: Discussionmentioning
confidence: 96%
“…In regard to NF1, a recent case report described effective treatment of the associated epilepsy with selumetinib in a patient who appeared to have dose‐dependent seizure control while receiving MEK inhibition for their glioma 30 . This patient had a bilateral OPG with extension into the hypothalamus, basal ganglia, and subcortical white matter, as well as a mass effect on the right insular cortex and focal symptomatic epilepsy lateralized to the right hemisphere.…”
Section: Discussionmentioning
confidence: 99%
“…Other targeted agents may also hold promise in this regard, including MEK inhibitors. 8 Further study of neurologic symptom control with targeted therapy versus traditional chemotherapeutic agents is needed to understand this effect.…”
mentioning
confidence: 99%